CHARACTER INTEGRATION IN MATHEMATICAL LEARNING AT ELEMENTARY SCHOOL (STUDY TO AL-KHWARIZMI'S THOUGHT) - Urip Meilina Kurniawati; Muqowim Muqowim (JIP Jurnal Ilmiah PGMI, 2021)
This study aims to analyze integration of character values in mathematics learning for Elemantry School (SD) or Islamic Elementary School (MI) in particular Al-Khwarizmi's perspective. In this study, the method used is a qualitative method with a library research approach. The data collection technique in this research is documentation. Documentation includes searching for data in the form of articles related to the results of Al-Khwarizmi's thought and mathematical learning in SD/MI. The analytical technique used is content analysis which is carried out by selecting, analyzing, comparing and combining the various opinions listed in the articles analyzed so that they are found that are more relevant. Al-Khwarizmi is one of the Muslim scientists who contributed to the field of mathematics and is called the father of al-jabar. The results of this study found that the results of Al-Khwarizmi's thought in the field of mathematics have a specialty in which his thought contain many character values ​​that can be imitated including religious value, discipline value, honest value, hard work value, critical, logical, creative thinking value. and innovative value, curiosity value, communicative value, independent value, responsibility value, self-confidence value, democracies value, reading value, and fair value, compassion, and friendship.